Specific Imaging of Inflammation with the 18kDa Translocator Protein Ligand DPA-714 in Animal Models of Epilepsy and Stroke - Harhausen, Denise; Sudmann, Violetta; Khojasteh, Uldus; Müller, Jochen; Zille, Marietta; Graham, Keith; Thiele, Andrea; Dyrks, Thomas; Dirnagl, Ulrich; Wunder, Andreas (PLOS ONE, 2013)
Inflammation is a pathophysiological hallmark of many diseases of the brain. Specific imaging of cells and molecules that contribute to cerebral inflammation is therefore highly desirable, both for research and in clinical application. The 18 kDa translocator protein (TSPO) has been established as a suitable target for the detection of activated microglia/macrophages. A number of novel TSPO ligands have been developed recently. Here, we evaluated the high affinity TSPO ligand DPA-714 as a marker of brain inflammation in two independent animal models. For the first time, the specificity of radiolabeled DPA-714 for activated microglia/macrophages was studied in a rat model of epilepsy (induced using Kainic acid) and in a mouse model of stroke (transient middle cerebral artery occlusion, tMCAO) using high-resolution autoradiography and immunohistochemistry. Additionally, cold-compound blocking experiments were performed and changes in blood-brain barrier (BBB) permeability were determined. Target-to-background ratios of 2 and 3 were achieved in lesioned vs. unaffected brain tissue in the epilepsy and tMCAO models, respectively. In both models, ligand uptake into the lesion corresponded well with the extent of Ox42- or Iba1-immunoreactive activated microglia/macrophages. In the epilepsy model, ligand uptake was almost completely blocked by pre-injection of DPA-714 and FEDAA1106, another high-affinity TSPO ligand. Ligand uptake was independent of the degree of BBB opening and lesion size in the stroke model. We provide further strong evidence that DPA-714 is a specific ligand to image activated microglia/macrophages in experimental models of brain inflammation.